Efeito do uso do solo na estrutura da comunidade de Lagartos do Cerrado - Gomes, Liara Ghisi (2019)
The expansion of agricultural activities is among the main factors that threaten biodiversity and ecosystem functions. Habitat change can cause changes in the composition and structure of communities. Co-occurrence and nesting are two ecological standards used to measure community structure. In this study I assessed how the diversity and type of land use affects the co-occurrence and nesting patterns of Cerrado lizard communities and guilds. I used information from published works, considering 25 sample points. The selected studies used, as capture methods, a set of interception and fall traps with guide fences and active collections in a total sampling period of at least 20 days. Co-occurrence patterns were analyzed using the C-score index and three null models. For nesting, the NODF index was used. This compilation included 47 species of lizards belonging to 13 families. Of the 47 species, 14 were classified as semi-fossorial, 16 as climbers, 12 as terrestrial and 5 as arboreal. The analyzes showed that communities and guilds present segregation patterns, and for the terrestrial guild, which presented an aggregate pattern in relation to the diversity of soil cover. For nesting, communities and guilds did not present a nested pattern. The patterns displayed in the communities were dependent on the diversity of the soil cover and the proportion of the area used for agriculture and livestock. Thus, communities have shown these patterns, as species can respond to different aspects of physical and biotic environments.